842 An audit to assess adherence to the Tongue Reduction Integrated Care Pathway for Beckwith Wiedemann Syndrome. (19th August 2022) - Howard, T; Gabuniya, N; Kerr, S; Cornejo, P
Abstract: Aim: Beckwith-Wiedemann Syndrome (BWS) is a congenital overgrowth syndrome that occurs in approximately 1 in 15, 000 births. A cardinal is macroglossia which can lead to sleep apnoea, difficulties feeding, speech, drooling and malalignment of teeth/jaw. Some children require tongue reduction surgery and are managed with a specific protocol to ensure the correct analgesia, fluid regime and commencement of oral feeds are delivered post-operatively. The aim of the audit was to improve adherence and awareness of the protocol to improve the patient journey. Method: Initial audit cycle between 22/01/21 – 03/02/21 in the form of anonymous staff survey. Following initial results staff underwent two separate teaching sessions and posters were applied in key wards and staff areas. Repeat audit was completed between 01/07/2021 – 01/08/2021. Results: Initial audit results demonstrated 44% (11/25) of ward staff were unaware of the Tongue Reduction Integrated Care Pathway and 56% (14/25) did not know which condition this protocol and surgical procedure was related to. Following both sets of interventions there was an improvement to 77.8% (14/18) of staff being aware of the protocol and 88.9% (16/18) of staff members knew which syndrome was associated with this pathology. Additionally, in the re-audit we demonstrated that 100% of participants were aware of the analgesia protocol. Correct rationale for fluid regime was demonstrated in 56% vs 24% demonstrating there is still room for improvement in this domain. Conclusion: We have demonstrated that through teaching and the implementation of a poster we have improved the awareness of the Tongue Reduction Protocol.